179k views
0 votes
3-(2c-8)=7 pls answer asap my homeworks almost late i need an answer fast

User Bill Lin
by
4.3k points

2 Answers

3 votes

Answer:

Explanation:

3 - 2c + 8 = 7

-2c + 11 = 7

-2c = -4

c = 2

User Starf
by
5.1k points
5 votes

Answer:

c=2

Explanation:

hope it helps :)

Simplifying

3 + -1(2c + -8) = 7

Reorder the terms:

3 + -1(-8 + 2c) = 7

3 + (-8 * -1 + 2c * -1) = 7

3 + (8 + -2c) = 7

Combine like terms: 3 + 8 = 11

11 + -2c = 7

Solving

11 + -2c = 7

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-11' to each side of the equation.

11 + -11 + -2c = 7 + -11

Combine like terms: 11 + -11 = 0

0 + -2c = 7 + -11

-2c = 7 + -11

Combine like terms: 7 + -11 = -4

-2c = -4

Divide each side by '-2'.

c = 2

Simplifying

c = 2

User Linbianxiaocao
by
4.5k points